Distinct gut microbiome features characterize Fasciola hepatica infection and predict triclabendazole treatment outcomes in Peruvian patients - Lee, Giljae; Rosa, Bruce A.; Fernandez-Baca, Martha V.; Martin, John; Ore, Rodrigo A.; Ortiz, Pedro; Cabada, Miguel M.; Mitreva, Makedonka (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundFasciola hepatica, a globally distributed helminth, causes fasciolosis, a disease with significant health and economic impacts. Variability in triclabendazole (TCBZ) efficacy and emerging resistance are remaining challenges. Evidence suggests that the gut microbiome influences host-helminth interactions and is associated with anthelmintic effects, but its association with human F. hepatica infection and TCBZ efficacy is not well understood.MethodsIn this study, we investigated the relationship between Fasciola hepatica infection and the gut microbiome through metagenomic shotgun sequencing of 30 infected and 60 age- and sex-matched uninfected individuals from Peru. Additionally, we performed a longitudinal analysis to evaluate microbiome dynamics in relation to TCBZ treatment response.Results and discussionInfection was associated with specific microbial taxonomic and functional features, including higher abundance of Negativibacillus sp900547015, Blautia A sp000285855, and Prevotella sp002299635 species, and enrichment of microbial pathways linked to survival under stress and depletion of pathways for microbial growth. Unexpectedly, we identified that responders to TCBZ treatment (who cleared infection) harbored many microbiome features significantly different relative to non-responders, both before and after treatment. Specifically, the microbiomes of responders had a higher abundance Firmicutes A and Bacteroides species as well as phospholipid synthesis and glucuronidation pathways, while non-responders had higher abundance of Actinobacteria species including several from the Parolsenella and Bifidobacterium genera, and Bifidobacterium shunt and amino acid biosynthesis pathways.ConclusionsOur findings underscore the impact of helminth infection on gut microbiome and suggest a potential role of gut microbiota in modulating TCBZ efficacy, offering novel insights into F. hepatica-microbiome interactions and paving the way for microbiome-informed treatment approaches.